Motored test rig design and fabrication for small engine testing - Rui Jin, Ho (2007)
Performance of a two-stroke engine is largely dependant on scavenging and trapping efficiency of a designed cylinder and port geometry. A motored test rig built specifically for high speed application is designed for 2-stroke spark ignition engine to allow further study and have better understanding of flow mechanism of the engine at high speed condition which will influence trapping and scavenging efficiency. A new concept and design is developed. Current available test rig in University Malaysia Pahang is limited to a low speed range of maximum of 1480rpm which is the main constraint to further experiment and understanding. A rigid designed test rig to allow assembly of small two-stroke engine, gearbox and induction motor and amplify induction motor rotating speed to provide wide RPM output using gearbox to provide a predetermined condition of operating two-stroke cycle engine to allow data acquisition on condition boundary for CFD simulation and experimental data. This new design of motored test rig will have the capability of testing engine at high speed by assembling a gearbox to multiply the speed of driving electric motor shaft of 1480 rpm into transmission input shaft to a maximum speed over 6000rpm at the transmission output shaft. Under motored condition, pressure transducer is applied and flush mounted at inlet port, scavenge port and cylinder. A crank encoder is used to define the condition to each crank angle of a rotation. As a result, data can be collected over a broader engine speed from data acquisition computer.